Nonsurgical management of soft tissue around the restorations of maxillary anterior implants: a clinical report - Seyedan K; Nahidi R (Tehran University of Medical Sciences, 2010)
"nBackground and Aims: Soft tissue management with providing the esthetic for restoration of a single implant in the anterior maxilla is of great importance. Tissue training helps to develop a proper emergence profile and natural tooth appearance. The aim of this article was to report a nonsurgical management of undesirable contours of soft tissue around maxillary anterior implants to achieve an optimum appearance. "nMaterials and Methods: A 23-year-old female with congenital missing of maxillary lateral incisors, after completion of a fixed orthodontic treatment and gain enough space, received 2 dental implants. After second phase surgery and healing period, construction of the restorations was not possible through conventional method because of severe soft tissue collapse. In this case, soft tissue contours were corrected using a provisional restoration and then final restoration was made and delivered. "nConclusion: Tissue training with a provisional restoration helps to re-establish normal gingival tissue contours and interdental papillae around the restoration of maxillary anterior implants.